2001
DOI: 10.1007/s003300100982
|View full text |Cite
|
Sign up to set email alerts
|

Hoffa's recess: incidence, morphology and differential diagnosis of the globular-shaped cleft in the infrapatellar fat pad of the knee on MRI and cadaver dissections

Abstract: We frequently observed a fluid-like indentation at the inferior posterior margin of Hoffa's fat pad of the knee and sought to establish the incidence and differential diagnostic criteria of this cleft. In total, 133 MRI studies and 35 cadaver specimens were analyzed for the location, size, and shape of clefts at the inferior posterior margin of Hoffa's fat pad. The incidence of a fluid-like ovoid cleft on MR images was 13.5% and in cadavers 14.3%. The cleft was located just below the insertion of the infrapate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 0 publications
2
39
1
1
Order By: Relevance
“…Articular fat pads are structurally similar to subcutaneous tissue [43], and it is assumed that they contribute to joint lubrication, stability, and absorption of forces generated in the moving joint [4][5][6][7]. For the infrapatellar fat pad, it has been shown that acute or repetitive trauma or surgery can induce hemorrhage and inflammation [6,44], subsequently leading to hypertrophy and impingement [16].…”
Section: Discussionmentioning
confidence: 99%
“…Articular fat pads are structurally similar to subcutaneous tissue [43], and it is assumed that they contribute to joint lubrication, stability, and absorption of forces generated in the moving joint [4][5][6][7]. For the infrapatellar fat pad, it has been shown that acute or repetitive trauma or surgery can induce hemorrhage and inflammation [6,44], subsequently leading to hypertrophy and impingement [16].…”
Section: Discussionmentioning
confidence: 99%
“…Its intra-articular surface is lined by synovial tissue, and there is a framework of fibrous cords within it in addition to the adipose tissue [2]. This fat pad is readily visible during routine MR imaging of the knee, and clefts or recesses along its posterior margin are frequently seen especially on sagittal MR images.…”
Section: Discussionmentioning
confidence: 96%
“…One of these clefts is close to the inferior border of the patella [1], and another that was recently described as the infrahoffatic recess ( Fig. 1) [2] lies anterior to the inferior portion of the infrapatellar plica (ligamentum mucosum) [1][2][3]. There is a single report in the literature only briefly mentioning the former of these recesses [1], and discrepancies exist among the two reports analyzing the latter recess in relatively large groups of subjects [2,3].…”
Section: Introductionmentioning
confidence: 90%
“…This is well illustrated by the synonymous use of the terms ''patellofemoral pain syndrome'' [5], ''chondromalacia patellae'' [14], ''patellofemoral dysfunction'' [11], ''patellofemoral arthralgia'' [28], ''Hoffa's syndrome'' [19] and ''anterior knee pain syndrome'' [25], to describe almost identical clinical symptoms. Garrick [8] found 11% of 16,748 Sports-related problems to be associated to anterior knee pain.…”
Section: Introductionmentioning
confidence: 99%